2010
DOI: 10.1089/jmf.2008.0159
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Antiproliferative Activities of Different Horsetail (Equisetum arvense L.) Extracts

Abstract: In this study we investigated antioxidative and antiproliferative activity of different horsetail (Equisetum arvense L.) extracts. The antioxidative activity was measured by the electron spin resonance (ESR) spectroscopy-spin trapping method. The influence of different horsetail extracts during lipid peroxidation of (1) sunflower oil induced by the lipophilic azo-initiator 4,4'-azobis(4-cyanovaleric acid) and (2) soybean phosphatidylcholine liposomes induced by the hydrophilic azo-initiator 2,2'-azobis(2-amidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 32 publications
3
63
0
1
Order By: Relevance
“…It is likely that a significant increase in antioxidant activity was associated with the composition of field horsetail extract. According to Cetojević-Simin et al (2010), field horsetail contains more than 10% inorganic substances (two-thirds of which are silicic acid and potassium salts). The results obtained suggest that the field horsetail extracts could be used as an easily accessible source of natural antioxidants and as potential phytochemicals (Cetojević-Simin et al, 2010, Romano et al, 2013.…”
Section: Fernandezmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that a significant increase in antioxidant activity was associated with the composition of field horsetail extract. According to Cetojević-Simin et al (2010), field horsetail contains more than 10% inorganic substances (two-thirds of which are silicic acid and potassium salts). The results obtained suggest that the field horsetail extracts could be used as an easily accessible source of natural antioxidants and as potential phytochemicals (Cetojević-Simin et al, 2010, Romano et al, 2013.…”
Section: Fernandezmentioning
confidence: 99%
“…According to Cetojević-Simin et al (2010), field horsetail contains more than 10% inorganic substances (two-thirds of which are silicic acid and potassium salts). The results obtained suggest that the field horsetail extracts could be used as an easily accessible source of natural antioxidants and as potential phytochemicals (Cetojević-Simin et al, 2010, Romano et al, 2013. Frias et al (2005) also have indicated that vitamin C increased sharply but gradually after germination and this processes caused a significant increase in Trolox equivalent antioxidant capacity (TEAC).…”
Section: Fernandezmentioning
confidence: 99%
“…Its extracts have shown significant anticancer activity against human prostate, breast, and colon cancer cells (Aydos et al, 2011;Durak et al, 2004;Guler, 2013;Konrad et al, 2000). Cytotoxicity toward several human cancer cell lines has demonstrated also for extracts prepared from Equisetum arvense L. (Equisetaceae) (field horsetail) and Secale cereale L. (Poaceae) (rye grass) (Cetojevic-Simin et al, 2010;Moodley & Shengwenyana;Sandhu et al, 2010); however, anticancer effects and potential oncological applications of these plants certainly need further investigation.…”
Section: Herbsmentioning
confidence: 99%
“…The mechanism of scavenging free radical reactive species is suggested as being caused by the action of electron-hydrogen donation. 41 Cetojević-Simin et al 56 conducted an in vitro study in which they investigated the antioxidative effect of 6 S. montana extracts on free radicals. Antioxidative activity increased dose-dependently.…”
Section: Results and Discussion Efficacymentioning
confidence: 99%